Digital transformation in information management - Mohamed, Nor Rashidah; Mustapa, Maziah (Universiti Teknologi MARA, Johor, 2025)
In the twenty-first century, information has become one of the most valuable resources in the world. It fuels progress, connects societies, and defines success across industries. Every day, billions of pieces of information are created, shared, and stored. Yet, information by itself is meaningless unless it is transformed into knowledge and used wisely. This transformation is what gives rise to knowledge power is the capacity to act intelligently and effectively through understanding.